Composition and properties of fly ash collected from a multifuel fluidized bed boiler co-firing refuse derived fuel (RDF) and hard coal. (1st November 2021) - Mlonka-Mędrala, Agata; Dziok, Tadeusz; Magdziarz, Aneta; Nowak, Wojciech
Abstract: In Poland, Refuse Derived Fuel (RDF) potential is significant, but high heterogeneity and contamination of the fuel limit its direct use in power industry. In this work samples were collected from a real-scale multifuel unit co-firing RDF with hard coal. Fuel samples and fly ashes collected from secondary cyclone and from bag filter were analysed in details. The thermal behaviour of fly ashes was investigated using X-ray diffraction (XRD), simultaneous thermal analysis (STA) and high-temperature microscope. High content of calcium compounds in both ash samples was noted. To determine the influence of flue gas treatment installation on the ash morphology and composition, Scanning Electron Microscopy with Energy Dispersive Spectroscopy (SEM-EDS) was used. Fly ash after flue gas treatment (FGT) system was much finer and higher content of heavy metals was observed. The mass distribution of mercury and leachability of selected heavy metals from the fly ashes were performed for the analysed unit. The concentration of mercury was several times higher in case of first collected fly ash due to longer contact time of flue gases with ash. Fly ashes contained high amounts of copper, lead and vanadium, but leachability of analysed metals was lower in case of bag filter ash. Highlights: Ashes from real unit of co-firing Refuse Derived Fuel and coal were investigated. The highest concentration of mercury was measured for fly ash before FGT system. The stability of heavy metals is higher in ash after FGT system. Sorbent injection influenced on fly ash composition, morphology and properties. Ashes were rich in calcium compounds, especially calcium sulphate.